2012
DOI: 10.1093/nar/gks670
|View full text |Cite
|
Sign up to set email alerts
|

Repair of cisplatin-induced DNA interstrand crosslinks by a replication-independent pathway involving transcription-coupled repair and translesion synthesis

Abstract: DNA interstrand crosslinks (ICLs) formed by antitumor agents, such as cisplatin or mitomycin C, are highly cytotoxic DNA lesions. Their repair is believed to be triggered primarily by the stalling of replication forks at ICLs in S-phase. There is, however, increasing evidence that ICL repair can also occur independently of replication. Using a reporter assay, we describe a pathway for the repair of cisplatin ICLs that depends on transcription-coupled nucleotide excision repair protein CSB, the general nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(174 citation statements)
references
References 78 publications
11
159
0
4
Order By: Relevance
“…Preparation of plasmid with a site‐specific cisplatin ICL (pICL), and ICL repair assays were performed as described (Räschle et al , 2008; Enoiu et al , 2012). Briefly pICL was incubated with HSS for 20 min, following addition of two volumes of NPE ( t  = 0) containing 32 P‐α‐dCTP.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of plasmid with a site‐specific cisplatin ICL (pICL), and ICL repair assays were performed as described (Räschle et al , 2008; Enoiu et al , 2012). Briefly pICL was incubated with HSS for 20 min, following addition of two volumes of NPE ( t  = 0) containing 32 P‐α‐dCTP.…”
Section: Methodsmentioning
confidence: 99%
“…31 It is cisplatin sensitive because of the lack of XPA activity, 29 which is a rate-limiting factor of the nucleotide excision repair (NER) system. 32 The A2780 ovarian carcinoma cell line, a model in cisplatin treatment, is also sensitive to this chemical.…”
Section: Cell Lines and Culturesmentioning
confidence: 99%
“…27 Considering all this, in this work we have tried to evaluate the cross-correlation of cisplatin-induced DNA adducts, intracellular Pt-content, cell cycle progression and drug-induced genomic instability (measured with the Comet assay), using four human cultured cell lines, A549, GM04312, A2780 and A2780cis, with different origins and cisplatin sensitivities. 23,28,29 Our final aim was to address the most accurate strategy to predict cisplatin sensitivity/resistance after short-time treatments with doses around the peak plasma concentration achieved in Pt-treated cancer patients. 30 …”
Section: Introductionmentioning
confidence: 99%
“…have the ability to bind to DNA and result in the formation of inter-strand crosslinks, while defects in replication and transcription pathways appear to enhance the sensitivity to cisplatin and mitomycin C treatments [72]. To these ends, NER appears to be the primary pathway activated for the removal of pyriplatin-DNA adducts formed in platinum-based treatments [73].…”
Section: Nucleotide Excision Repair (Ner)mentioning
confidence: 99%
“…To these ends, NER appears to be the primary pathway activated for the removal of pyriplatin-DNA adducts formed in platinum-based treatments [73]. On the contrary, work by other groups (in utilizing normal human fibroblasts along with NER deficient ones) have shown no beneficial effect of hyperthermia in enhancing sensitivity to cisplatin, regardless of NER deficiency or not [74] suggesting the contribution of other DNA repair pathways, such as TLS [72]. Finally, in vivo studies utilizing a murine metastatic ovarian cancer model have also shown that hyperthermia can contribute to the sensitization of tumors against cisplatin by inhibiting NER [75].…”
Section: Nucleotide Excision Repair (Ner)mentioning
confidence: 99%